IMMOBILIZATION OF RECOMBINANT LIPASE ENZYME ITB 1.2 ON NICKEL FOAM FOR FATTY ACID PRODUCTION IN ROTATING BED REACTOR (RBR) - Panjaitan, Wilda
Currently, the sector manufactures fatty acids using exceedingly energy-consuming techniques, like the Colgate-Emery and Twitchell approaches. These methods involve acid-catalyzed or non-catalyzed reactions with water-elevated temperatures of at least 250°C and a pressure of nearly 50 bars. While these extreme conditions enhance solubility between oil and water, reduce oil viscosity, and facilitate rapid reaction kinetics, the industrial process has significant drawbacks. They necessitate expensive equipment, resulting in high operating costs, consuming substantial energy, and producing undesired side reactions such as polyunsaturated fatty acids (PUFAs) polymerization, valuable components in vegetable oils Employing catalytic hydrolysis with enzyme biocatalysts offers a sustainable approach to address these challenges. To enhance the lifespan and reusability of lipase, endeavors are being made to optimize its utilization by immobilizing it Hence, this study aims to immobilize lipase onto Ni foam and investigate its application in producing fatty acids. Ni foam offers high porosity and low bulk density, which mitigate pressure drop effects and also enhance diffusion rates during reactions. Ni foam has a high affinity with recombinant lipase and high mechanical stability strength, which is suitable for enzymatic catalysis in Rotating Bed Reactor (RBR)